2019
DOI: 10.1002/adfm.201806863
|View full text |Cite
|
Sign up to set email alerts
|

Drawing a Pencil‐Trace Cathode for a High‐Performance Polymer‐Based Li–CO2 Battery with Redox Mediator

Abstract: Lithium-carbon dioxide (Li-CO 2 ) batteries have received wide attention due to their high theoretical energy density and CO 2 capture capability. However, this system still faces poor cycling performance and huge overpotential, which stems from the leakage/volatilization of liquid electrolyte and instability of the cathode. A gel polymer electrolyte (GPE)-based Li-CO 2 battery by using a novel pencil-trace cathode and 0.0025 mol L −1 (M) binuclear cobalt phthalocyanine (Bi-CoPc)-containing GPE (Bi-CoPc-GPE) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 46 publications
(72 reference statements)
1
54
0
Order By: Relevance
“…gas. Subsequently, after introducing pure Ar gas into such discharged battery to completely eliminate the residual CO2, such Li-CO2 battery was recharged to 5000 mAh g -1 for detecting the gas emission during the charge process [29,64]. Accordingly, three different points (A, B and C) were sequentially taken from the charge process in Fig.…”
Section: Analysis Of I-ru4cu1/cnfs Cathode Electrode After Discharge-mentioning
confidence: 99%
See 1 more Smart Citation
“…gas. Subsequently, after introducing pure Ar gas into such discharged battery to completely eliminate the residual CO2, such Li-CO2 battery was recharged to 5000 mAh g -1 for detecting the gas emission during the charge process [29,64]. Accordingly, three different points (A, B and C) were sequentially taken from the charge process in Fig.…”
Section: Analysis Of I-ru4cu1/cnfs Cathode Electrode After Discharge-mentioning
confidence: 99%
“…Electrocatalysts utilized to facilitate the kinetics of discharge and charge processes in Li-CO2 batteries have been extensively studied [18], such as carbon nanomaterials [19,20], transition metals [12,15,[21][22][23][24], metal oxides [25,26], metal carbides [27,28] and redox mediator [29]. Zhang and co-workers introduced carbon nanotubes as cathode catalyst in rechargeable Li-CO2 batteries [30], which showed a discharge capacity of 5786 mAh g -1 and cycling performance of 20 cycles at current density of 100 mA g -1 .…”
Section: Introductionmentioning
confidence: 99%
“…Li et al demonstrated a gel-polymer electrolyte containing a small amount of binuclear cobalt phthalocyanine (Bi-CoPc) that could significantly lower the overpotential of Li-CO 2 cells (as discussed in Section 3.3). [47] As discussed in Section 3.1, quinones could serve as an RM to mediate CO 2 reduction in Li-CO 2 cells. [43] Yin et al found that the interaction of quinones with CO 2 could lower the activation energy of CO 2 .…”
Section: Soluble Catalysts and Rmsmentioning
confidence: 99%
“…[ 46 ] Later, Li et al designed a gel–polymer with an ingredient of binuclear cobalt phthalocyanine (Bi‐CoPc). [ 47 ] The integrated Bi–CoPc could serve as a catalyst to promote the reduction of CO 2 . The Li–CO 2 cell with this polymer–electrolyte showed a reduced overpotential and a high discharge capacity.…”
Section: Electrolytes For Li−co2 Batteriesmentioning
confidence: 99%
“…Although the Li-CO 2 cell effectively captures CO 2 gas during the discharge process, the high charge overpotential caused by the insulating and insoluble characteristics of Li 2 CO 3 in the aprotic electrolyte should be reduced to prevent the severe parasitic reaction 7,15,16,23 . Therefore, most recent research on Li-CO 2 cells has focused on developing air-breathing cathodes such as metal catalysts, mediators, and metal oxide materials for reducing the charge overpotential and increasing the cycle ability 8,18,[24][25][26][27][28] . However, because of the sluggish electron transfer in the Li 2 CO 3 insulator, most of the reported studies investigated Li-CO 2 cells with mild current densities (Supplementary Table 1), which are not appropriate for high-performance battery applications, the limiting factor for the CO 2 capture rate; thus, enhancement of the rate performance certainly is advantageous to facilitate practical future battery and CO 2 storage applications of Li-CO 2 cell.…”
mentioning
confidence: 99%